Cisplatin ototoxicity and role of antioxidant on its prevention. (1st October 2020) - Fetoni, Anna Rita; Astolfi, Laura
Abstract: Objective: Highlight the novelties of cisplatin ototoxicity and its prevention, focussing on the role of oxidative stress. Methods: We screened various electronic databases and selected the reports concerning clinical data and animal and in vitro models investigations related to cisplatin-induced ototoxicity and or its prevention by antioxidants. Results: Clinical evidence showed that great advances have been made in the chemotherapy outcomes; nevertheless, the ototoxicity, mainly in paediatric patients, is a crucial issue that must be solved. In vitro and in vivo models were pivotal to deeply describe the toxic effect of the cisplatin and which are the mechanisms of action. These knowledges will help the researcher to improve the chemotherapy protocols in order to avoid the adverse effects without compromise the antitumoral action. Conclusion: Antioxidants seem to be the most promising drugs among the large number of substances tested against cisplatin ototoxicity, however, the inflammatory pathway must be taken into consideration.